The expression of thyroid hormone receptors (THR) is regulated by the progesterone receptor system in first trimester placental tissue and in BeWo cells in vitro. (December 2015) - Vattai, Aurelia; Ziegelmüller, Brigitte; Kost, Bernd; Kuhn, Christina; Hofmann, Simone; Bayer, Birgit; Anslinger, Katja; Jeschke, Udo; Ditsch, Nina
Abstract: Background: Thyroid hormones are essential for the maintenance of pregnancy and a deficiency in maternal thyroid hormones has been associated with early pregnancy losses. The aim of this study was a systematic investigation of the influence of mifepristone (RU 486) on the expression of the thyroid hormone receptor (THR) isoforms THRα1, THRα2, THRβ1 and THRβ2 on protein and mRNA-level. Methods: Samples of placental tissue were obtained from patients with mifepristone induced termination of pregnancy ( n  = 13) or mechanical induced termination of normal pregnancy ( n  = 20), each from the 4th to 13th week of pregnancy. Expression of THRα1, THRα2, THRβ1 and THRβ2 was analysed on protein level by immunohistochemistry and on mRNA level by real time RT-PCR (TaqMan). The influence of progesterone on THR gene expression was analysed in the trophoblast tumour cell line BeWo by real time RT-PCR (TaqMan). Results: Nuclear expression of THRα1, THRα2 and THRβ1 is downregulated on protein level in mifepristone (RU 486) treated villous trophoblast tissue. In decidual tissue, we found a significant downregulation only for THRα1 in mifepristone treated tissue. On mRNA level, we also found a significantly reduced expression of THRA but no significant downregulation for THRB in placental tissue. The gene THRA encodes the isoform THRα and the gene THRB encodes the isoform THRβ. The majority of cells expressing the thyroid hormone receptors in the decidua are decidual stromal cells. In addition, in vitro experiments with trophoblast tumour cells showed that progesterone significantly induced THRA but not THRB expression. Conclusions: Termination of pregnancy with mifepristone (RU 486) leads to a downregulation of THRα1, THRα2 and THRβ1 in villous trophoblasts and in addition to a decreased expression of THRA in placental tissue. Decreased expression of THRα1 induced by RU486 could also be found in the decidua. Therefore inhibition of the progesterone receptor may be responsible for this downregulation. This assumption is supported by the finding, that stimulation of the progesterone receptor by progesterone itself up-regulated THRA in trophoblast cells in vitro .